Political and Cosmic Symbolism in Genesis 14 and in Its Babylonian Sources - Astour, Michael С. (1966)
spez. 74-81: The Personal and Geographical Names in Gn 14; 81-100: The Characters and Historical References in the “Chedorlaomer Texts”; 100-109: Religious Philosophy of History and Cosmic Symbolism. Umfangreiches keilschriftliches Material.